Reklamasi Lahan Bekas Tambang Bijih Besi di Nagari Lolo Kecamatan Pantai Cermin Kabupaten Solok - Sriwinda 22 12; Helfia Edial; Dedi hermon (JURUSAN GEOGRAFI FIS UNP, 2018)
ABSTRACT This study is aimed to: (1) Knowing the physical characteristics of former iron ore mine land. (2) Propose appropriate land reclamation methods for the area of iron ore mine. The method used is quantitative research to know land characteristic and effort to select technique of land reclamation with unit of mapping that is land unit through overlay map of unit of land form with slope map, geology map, land map, and land use map. Sampling with Purposive Sampling method, with data analysis that is scoring method and garding. Result of research: (1) Land characteristic of research area are: tropical climate with annual average rainfall 2224 mm/yr, beveled and oblique tilted rock layers, mountains of denudational hills and alluvial fans, sloping slope, steep and very steep, sandy ground texture and sandy clay, single ground grain structure and plate, low soil fertility, ground water depth> 500 cm and land use dominated by shrubs /grasslands. (2) The proposed land reclamation method for former iron ore mine in Nagari Lolo is revegetation, ie planting the appropriate plant for former iron ore mine, especially pine plants.